2012 4th International Conference on Intelligent and Advanced Systems (ICIAS2012) 2012
DOI: 10.1109/icias.2012.6306167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of movie clips on human brain

Abstract: In this paper, we investigated the changes in brain activation with respect to watching movie clips in order to understand its effect on human brain. Electroencephalography (EEG) data was recorded using 24-channel EEG machine while subjects watched the movie clips. 14 male subjects were recruited for this research project. Two conditions were used in collecting EEG data; i) under eyes open condition while subjects looking at a white screen for five minutes and ii) while subjects watched selected movie clips fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition to ISC, researchers focus on depicting detailed patterns of cerebral activity with video or movie situations, for example, scanning deep areas in the brain [16,24], finding the connection between regions [29], and testing and comparing differences between viewers' brain responses and their subjective experience. In recent years, the brain-controlled films emerged, which enables the audience to engage with the content they are viewing [39,40,43], and the resulting movie no longer has a single directional feeding.…”
Section: Neurocinematicsmentioning
confidence: 99%
“…In addition to ISC, researchers focus on depicting detailed patterns of cerebral activity with video or movie situations, for example, scanning deep areas in the brain [16,24], finding the connection between regions [29], and testing and comparing differences between viewers' brain responses and their subjective experience. In recent years, the brain-controlled films emerged, which enables the audience to engage with the content they are viewing [39,40,43], and the resulting movie no longer has a single directional feeding.…”
Section: Neurocinematicsmentioning
confidence: 99%
“…Previous studies evaluated other stimuli (music, movie, illumination, vibration and odor) based on physiological responses of the central nervous system [9][10][11][12][13][14][15][16][17][18][19][20][21]. First, listening to relaxing music has been found to increase power spectrum components of the α-wave [9] and θ-wave [10] of the EEG signal and to decrease cerebral blood flow in the frontal lobe [11].…”
Section: Previous Studies On Brain Activitymentioning
confidence: 99%
“…First, listening to relaxing music has been found to increase power spectrum components of the α-wave [9] and θ-wave [10] of the EEG signal and to decrease cerebral blood flow in the frontal lobe [11]. Second, in a study of movie and image presentation, Aamir et al [12] reported that watching movie clip increased absolute α-wave power in occipital, parietal, frontal and motor regions compared to baseline. Additionally, Sakamoto et al revealed cerebral blood flow in the frontal lobe is an indicator of video comfort or discomfort [13].…”
Section: Previous Studies On Brain Activitymentioning
confidence: 99%
See 1 more Smart Citation